2010
DOI: 10.1021/jp106514g
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectroscopy of Helical Porphyrin Nanotubes

Abstract: We report polarized resonance Raman data of tetrakis(4-sulfonato)phenyl porphyrin (TSPP) aggregates in solution and deposited on Au(111) at wavelengths resonant with the red-shifted (J-band) and blue-shifted (H-band) components of the split Soret (B) band. We also report scanning tunneling microscopy (STM) images which reveal that the aggregate on Au(111) is a nanotube with a 2 nm wall thickness which tends to flatten on the substrate. Relative Raman intensities and their dependence on polarization of the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 39 publications
8
41
0
Order By: Relevance
“…Among the various local structural motifs, these porphyrins are able to interact adopting an edge-to-edge (J-type) or a side-by-side (H-type) geometry, each leading to specific spectroscopic features in terms of bathochromic or hypsochromic shifts in the corresponding UV/Vis electronic spectra [11]. Strong electronic coupling among the chromophores is responsible for resonant enhancement of Rayleigh [12][13][14][15][16][17][18][19][20] and Raman light scattering [21][22][23][24][25] and non-linear optical effects in large J-aggregates [26][27][28][29][30][31]. In addition, peculiar chiroptical properties emerge when these supramolecular systems grow in the presence of chemical [22,[32][33][34][35][36][37][38][39][40][41][42] or physical chiral bias [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various local structural motifs, these porphyrins are able to interact adopting an edge-to-edge (J-type) or a side-by-side (H-type) geometry, each leading to specific spectroscopic features in terms of bathochromic or hypsochromic shifts in the corresponding UV/Vis electronic spectra [11]. Strong electronic coupling among the chromophores is responsible for resonant enhancement of Rayleigh [12][13][14][15][16][17][18][19][20] and Raman light scattering [21][22][23][24][25] and non-linear optical effects in large J-aggregates [26][27][28][29][30][31]. In addition, peculiar chiroptical properties emerge when these supramolecular systems grow in the presence of chemical [22,[32][33][34][35][36][37][38][39][40][41][42] or physical chiral bias [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, it has been reported that self-assembly of monodisperse gold colloid particles into monolayers on polymer-coated substrates produces highly reproducible macroscopic surfaces active for surface-enhanced Raman scattering (SERS) [31]. In fact, many spectroscopic studies on the interaction of AuNPs with porphyrins and their aggregates in solution and on surfaces have been reported [32,33,34,35,36]. In this particular area, our interest has focused on the J-aggregates of tetrakis(4-sulfonatophenyl)porphyrin (TPPS) [37,38,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their manifold applications, various reports have dealt with the immobilization of J-aggregated porphyrins on substrates, highlighting the importance of the deposition step [45]. In particular, microscopic analysis has revealed the presence of differently shaped aggregates, such as rod, and nanotubular structures, depending on the experimental conditions [35,43,46]. Moreover, a detailed study has revealed that porphyrin concentration strongly affects the amount of J-aggregate adsorbed onto glass surfaces, showing a higher number of adsorbed entities at lower porphyrin concentrations [47].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 In this field, RR was also employed in detecting structural alterations in photosynthetic antenna complexes of green bacteria, 30 or in the design and testing of new anti-malaria drugs by sensing structural information on porphyrin moieties in hemes. 31 Different selforganized systems widely employed in supramolecular chemistry such as porphyrins 32,33,34 or carotenoids 35 have also been structurally monitored by RR. Moreover, RR spectroscopy has been adopted in the field of biosensors to accurately measure the strength of host-guest complexations.…”
Section: Introductionmentioning
confidence: 99%